HUBUNGAN ANTARA KEBIASAAN MAKAN PAGI DENGAN PRESTASI BELAJAR PADA ANAK KELAS IX SMPN 6 KOTABARU - Triyogo - (STKIP Paris Barantai, 2010)
This research aim to know and analyses about there is not of the relation of habit of breakfast with achievement of learning at class IX In SMPN 6 kotabaru. Result of this research hoped able to give input especially to the side of school that consumption of breakfast can influence achievement learning and with such a situation can be made consideration that the side of school is more paying attention toly is situation of its the protege is especially about habit of breakfast and gives experience to student in the application of science in school with research done in the school. Population in this research is all class school childs IX in SMPN 6 Kotabaru in 2009 amounts students technique sampling in this research applies purposive sampling because in its the sampling researcher considers something retrieval characteristic, that is sample taken is Firstly class IX familiarizing to take breakfast but having equivalent recall. Based on the rule is obtained by sample 35 students. Variable in this research is habit of breakfast as independent variable and achievement of learning as dependent variables.Kata-Kata KunciKebiasaan-Makan Pagi-Prestasi-Belajar dan pertumbuhan -Anak.